The impact of the single exit price policy on a basket of generic medicines in South Africa, using a time series analysis from 1999 to 2014. - Rajatheran Moodley; Fatima Suleman (PLoS ONE, 2019)
Background Regulating pharmaceutical markets have become a key strategy by most governments in ensuring the availability and accessibility of quality medicines to its citizens. The South African government, when faced with high medicine prices, implemented the Single Exit Price (SEP) in 2004. This study assessed the impact of the of the Single Exit Price (SEP) regulation introduced in South Africa in 2004 on a basket of generic. Method Private sector price data of a basket of medicines (December 1999 to December 2014) was obtained from various price files (Pharmacy Software Vendors and Community Pharmacy). The price of the medicine was expressed in a single unit dose. The medicines investigated used the WHO/HAI methodology. The Interrupted Time-Series (ITS) model was used to estimate the change in slope and level of medicines investigated (50 originator and its available generics) before and after the policy change. Results Majority of the medicines analysed reflect a substantial decrease in medicine prices immediately after implementation of the pricing regulations as reflected in both the change in level and the change in slope using the interrupted time series analysis. Discussion This study indicates that the SEP regulation had an impact on medicine pricing in South Africa in both the short (immediately on the introduction) and long term (over the study period). Most medicines investigated showed a smaller yearly increase in price compared to before regulations. Conclusion This study provides evidence of the impact of medicine pricing intervention from a middle-income country, and useful lessons can be drawn by other developing countries looking at introducing medicine price controls.